Change or Continuity of Social Protection Policies in Chile in Center-Left and Center-Right Governments - Martin Munchmeyer, María Pía (Revista del CLAD Reforma y Democracia, 2016)
From the analysis of welfare policy change, this paper aims to examine the axes of change and continuity of social policies in Chile, in a context of political stability and economic growth, but with changing political sign of government when assumed a right-wing government after two center-left governments, both with strong emphasis on social reforms. The study seeks to contribute to the reflection and study of the influence of the political orientation of government on social protection policies, and contribute to the analysis of Latin American social protection systems. From analysis of the regulatory frameworks of the contents of the main reforms and social programs, the level, direction, extent and dynamics of change that occurred in the right government after two reformist center-left governments. We conclude that for the Chilean case there is not retrenchment. There is not a paradigmatic change, but it is an incremental change with policy orientation changes on social policies with a re-commodification process through privatization and conditionality of social rights, in an approach that what matters opportunities are created from the economic growth and by the market. The right government emphasizes the importance of targeting policies, and increases the assistencial offer, going against the left government universalist option that was increasing the rights to social protection. The dynamics of change is gradual and incremental and degree of transformation is the continuity of the model of social policies, but with a strong role of private providers and a reduction of social expenditures. The center-left and right governments showed significant progress in reducing poverty, although the challenge of inequality remained as a pending task.